ANALISIS POSTUR KERJA PADA KARYAWAN BENGKEL WARLOK BARBEKU MULTI SERVIS DENGAN MENGGUNAKAN REBA - Krisna Dewanti, Galuh; Perdana, Surya; Tiara, Tiara (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2020)
The wrong working position when electronic service will cause the body to become sick and the service time becomes longer. The purpose of this study was to determine the work position of employees and find out the results of REBA, as well as provide suggestions for improving work posture. This research method uses the REBA method. The results of this study indicate the work position of employees, namely: Hand movements form an angle of 90 °. The movement of the lower arm forms an angle > 60 °. Curved wrist movements form an angle of > 15 ° and then the wrist rotates. Neck movements form an angle of 45 °, and tilt sideways. Back curved into an angle > 66 ° and tilted to the right and left. Squat posture, legs are not fully supported, and the weight is not spread evenly. The final score from the REBA Assessment is 12 for the right position and 11 for the left position, which means that the level of work posture risk is very high and corrective action is needed at this time. It is proposed to add tools such as tables for the placement of washing machines and chairs for working employees.